2003
DOI: 10.1021/ic020640y
|View full text |Cite
|
Sign up to set email alerts
|

DFT Calculations of Isomer Shifts and Quadrupole Splitting Parameters in Synthetic Iron−Oxo Complexes:  Applications to Methane Monooxygenase and Ribonucleotide Reductase

Abstract: To predict isomer shifts and quadrupole splitting parameters of Fe atoms in the protein active sites of methane monooxygenase and ribonucleotide reductase, a correlation between experimental isomer shifts ranging 0.1-1.5 mm s(-)(1) for Fe atoms in a training set with the corresponding density functional theory (DFT) calculated electron densities at the Fe nuclei in those complexes is established. The geometries of the species in the training set, consisting of synthetic polar monomeric and dimeric iron complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(96 citation statements)
references
References 63 publications
(80 reference statements)
6
89
1
Order By: Relevance
“…(7), (17), and (19), depends of the choice of the atomic orbital basis set and on the choice of density functional employed [58,77,81,82,[90][91][92][124][125][126][127][128][129][130]. It has been suggested that, for every combination of basis set and approximate density functional, an individual value of the calibration constant should be obtained [81,82].…”
Section: Density Functional and Ab Initio Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…(7), (17), and (19), depends of the choice of the atomic orbital basis set and on the choice of density functional employed [58,77,81,82,[90][91][92][124][125][126][127][128][129][130]. It has been suggested that, for every combination of basis set and approximate density functional, an individual value of the calibration constant should be obtained [81,82].…”
Section: Density Functional and Ab Initio Calculationsmentioning
confidence: 99%
“…In the calculations on iron (as well as on some other elements), the non-relativistic quantum chemical formalism is usually employed in connection with the cluster approach [77,[80][81][82]85,86,88,89,103,104,[124][125][126][127][128][129][130]. The so-obtained contact densities are corrected for relativistic effects with the use of scaling factor S (Z).…”
Section: Inclusion Of Relativistic Effectsmentioning
confidence: 99%
“…Thus, it can be determined to good accuracy (often better than 0.1 mm s -1 ) from ground-state DFT calculations using a suitable method-specific calibration procedure on the basis of a linear correlation between the calculated electron density at the nucleus versus the measured d Liu et al 2003;Neese 2002;Sinnecker et al 2005;Zhang et al 2002). The predicted d is in good agreement with experimental data when using B3LYP-calibrated curves in combination with basis sets that are flexible in the core region and extensively polarized (Berry et al 2008;Schoneboom et al 2005;Sinnecker et al 2005).…”
Section: Mössbauer Spectroscopymentioning
confidence: 99%
“…Han and Noodleman have proposed several correlation formula by doing linear regression fit of the calculated ρ(0) and δexp isomer shift, IS, as well as for the quadrupole splitting, QS, on large sets of experimentally availble data and using different theoretical models [14][15][16]. By using some of the proposed correlations, we attempted to find explanation of the experimentally observed Mössbauer spectral features and propose the most probable structure of the Fe(II) complex of 2AID.…”
Section: Introductionmentioning
confidence: 99%